2009
DOI: 10.1897/08-419.1
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of oral hexahydro‐1,3,5‐trinitro‐1,3,5‐triazine in the western fence lizard (Sceloporus occidentalis)

Abstract: Hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) has been widely used as an explosive in munition formulations, resulting in contamination of wildlife habitat on military installations. To estimate health effects for reptilian species, acute, subacute, and subchronic oral toxicity studies were conducted using the Western fence lizard (Sceloporus occidentalis). Estimated oral median lethal doses were 72 (95% confidence interval [CI], 49-106) mg/kg body weight (slope, 3.754) for males and 88 (95% CI, 65-119) mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
(82 reference statements)
1
13
0
Order By: Relevance
“…These findings are in accordance with our results. Similar findings such as seminiferous tubular degeneration, abnormal spermatogenesis and sloughing were observed in S. occidentalis (McFarland et al 2009). Oedema and haemorrhage were also reported in the interstitial tissue of the testes of rats exposed to (Afifi et al 1991), cadmium (Shimada et al 2009) like in O. elegans exposed to carbaryl.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These findings are in accordance with our results. Similar findings such as seminiferous tubular degeneration, abnormal spermatogenesis and sloughing were observed in S. occidentalis (McFarland et al 2009). Oedema and haemorrhage were also reported in the interstitial tissue of the testes of rats exposed to (Afifi et al 1991), cadmium (Shimada et al 2009) like in O. elegans exposed to carbaryl.…”
Section: Discussionsupporting
confidence: 78%
“…Effects of methyl thiophanate on liver (Buono et al 2007), on adrenal gland (De Falco et al 2007), on thyroid (Sciarrillo et al 2008) were examined in a lizard, Podarcis sicula. Toxic effects of oral hexahydro-1,3,5-triazine and 2-amino-4,6-dinitrotoluene were also studied in terms of histopathologic changes in S. occidentalis (McFarland et al 2009(McFarland et al , 2011.…”
mentioning
confidence: 99%
“…Dosing was prepared according to those described previously with modifications (Di Renzo et al, 2009;McFarland et al, 2011McFarland et al, , 2009Suski et al, 2008). TF was first dissolved in the ethanol (analytical grade, Beijing Chemical Reagent Co. Ltd, China) then dispersed in corn oil (ethanol:corn oil was 1:9, v/v).…”
Section: Dosingmentioning
confidence: 99%
“…Similarly, MCs affect reproductive organs in the WFL. Earlier studies (McFarland et al 2008(McFarland et al , 2009) have demonstrated a negative influence on testes mass and abnormal histopathology in lizards exposed to 2,4,6-trinitrotoluene (TNT) and 1,3,5-trinitro-1,3,5-triazine (RDX).…”
Section: Introductionmentioning
confidence: 99%